Special educational needs: Do we know how to educate? - Tomé, José Manuel Salum (Advances in Social Sciences Research Journal, 2020)
This article reports the results that its objective is to analyze the evolution of political discourse in Chile on special educational needs, as well as to analyze the relationship of the discourse with the main public policy initiatives regarding legislation, fiscal budget and direct executive action. It can be seen that it is possible to identify important changes in the use of the main concepts, emphasis and discussions associated with the promotion of inclusive education. In addition, there is growing interest in the issue of diversity, both nationally and internationally, which is expressed in increasingly specific public policy initiatives to promote inclusive education. However, there are still gaps and gaps between political discourse and policy initiatives, as well as between the approach of public policies in Chile and the state of art of the international discussion on the subject.